Happiness, values & society - Gross National Happiness in Bhutan - Lessons for the UK? - Keegan, Sheila (Henry Stewart Talks, 2008)
Exploration and comparison of the relationship between wealth, values and happiness in the UK and Bhutan, Historical and cultural developments in Bhutan which have led to a policy of Gross National Happiness (GNH), How GNH is translated into practice, What lessons can we learn for the UK?